Role of nitric oxide and prostaglandin in the maintenance of cortical and renal medullary blood flow - Gomez,S.I (2008)
This study was undertaken in anesthetized dogs to evaluate the relative participation of prostaglandins (PGs) and nitric oxide (NO) in the maintenance of total renal blood flow (TRBF), and renal medullary blood flow (RMBF). It was hypothesized that the inhibition of NO should impair cortical and medullary circulation because of the synthesis of this compound in the endothelial cells of these two territories. In contrast, under normal conditions of perfusion pressure PG synthesis is confined to the renal medulla. Hence PG inhibition should predominantly impair the medullary circulation. The initial administration of 25 µM kg-1 min-1 NG-nitro-L-arginine methyl ester produced a significant 26% decrease in TRBF and a concomitant 34% fall in RMBF, while the subsequent inhibition of PGs with 5 mg/kg meclofenamate further reduced TRBF by 33% and RMBF by 89%. In contrast, the initial administration of meclofenamate failed to change TRBF, while decreasing RMBF by 49%. The subsequent blockade of NO decreased TRBF by 35% without further altering RMBF. These results indicate that initial PG synthesis inhibition predominantly alters the medullary circulation, whereas NO inhibition decreases both cortical and medullary flow. This latter change induced by NO renders cortical and RMBF susceptible to a further decrease by PG inhibition. However, the decrease in medullary circulation produced by NO inhibition is not further enhanced by subsequent PG inhibition.